Social capital in the perspective of the theory of resources and capabilities: a bibliometric analysis - López Inda, Karina Azucena; Alvarado Altamirano, Sergio; Fong Reynoso, Carlos; González Álvarez, Eleazar (Unidad Editorial UPTC, 2020)
In this study, a first approach is made to the integrated perspective of social capital under the Theory of Resources and Capabilities. For this purpose, the Scopus database was selected, from which the necessary information was extracted to perform a bibliometric analysis of citation, keywords and authorship with the support of the Excel and VOSviewer tools. Likewise, a content review was applied to the 46 documents that the search showed. The results confirm that social capital is seen as a firm resource that contributes to improving performance and the formation of sustainable competitive advantages, as well as being closely linked to the use of human capital and the development of skills such as innovation, learning, adaptation, as well as knowledge management. Keywords: Resources and capabilities theory (RBT), social capital, competitive advantage, innovation JEL Codes: M10, M53, O12, O31. Received: 24/10/2016. Accepted: 10/02/2020.  Published: 27/04/2020